Pengembangan Video Animasi Powtoon pada Pembelajaran Fisika Terintegrasi STEM terhadap Hasil Belajar Peserta Didik - Tresiadi, Revika; Jumini, Sri; Fatiatun, Fatiatun (Universitas Pendidikan Mandalika, 2024)
This study aimed to develop Powtoon animated videos for STEM-integrated physics learning and assess their impact on student learning outcomes. The Research and Development (R&D) method, using the ADDIE model, was employed to systematically develop and evaluate the instructional media. The study involved five phases: analysis, design, development, implementation, and evaluation. During the analysis phase, needs were identified based on observations of students' difficulties in understanding abstract physics concepts and their disengagement from traditional teaching methods. The videos were developed to integrate scientific, technological, engineering, and mathematical (STEM) concepts, focusing on simple machines such as levers and pulleys. Expert validation was conducted to assess the quality of the videos, and revisions were made accordingly. The implementation phase involved a pretest-posttest control group design with eighth-grade students from SMP Negeri 2 Watumalang. The experimental group used the STEM-integrated Powtoon videos, while the control group received traditional instruction. Data were analyzed using a t-test and N-Gain to measure the improvement in student learning outcomes. Results showed a significant improvement in the experimental group’s post-test scores, with an average N-Gain of 66.95%, categorized as moderately effective. The control group had a lower average N-Gain of 49.22%, categorized as less effective. The findings demonstrate that the Powtoon videos not only enhanced students' conceptual understanding but also increased their motivation and engagement in physics learning. These results suggest that integrating STEM principles into instructional media, such as animated videos, is an effective strategy for improving learning outcomes in physics. The study recommends expanding the use of such multimedia approaches across other STEM-related subjects to foster critical thinking and problem-solving skills in students.